1995
DOI: 10.1007/bf01719487
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro efficacy of the disinfectant Virkon

Abstract: A study was conducted on a new acid peroxygen system based disinfectant (Virkon), in order to assess its in vitro efficacy. The chemical was tested on different bacteria (Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli), spores (Bacillus subtilis) and on the Hepatitis B surface antigen (HBsAg), and compared in its activity with phenol and glutaraldehyde (calculation of the 'phenol coefficient' and the 'glutaraldehyde coefficient'). The constancy of speed of disinfection, the coefficient of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 0 publications
0
27
1
Order By: Relevance
“…Coates and Wilson (1992) mentioned that Virkon-S at 1% (w/v) had a marked bactericidal action on nonsporulating bacteria. Gasparini et al (1995) found that Virkon-S at a concentration of 1% had a bactericidal action against Staphylococcus aureus, Pseudomonas aeruginosa, and E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coates and Wilson (1992) mentioned that Virkon-S at 1% (w/v) had a marked bactericidal action on nonsporulating bacteria. Gasparini et al (1995) found that Virkon-S at a concentration of 1% had a bactericidal action against Staphylococcus aureus, Pseudomonas aeruginosa, and E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…The results clearly indicate that the efficiency of the disinfectant depends on concentration of the compound and the exposure time. Gasparini et al (1995) found that slight increases in Virkon-S concentration greatly reduced the contact time needed to inactivate the microorganism.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 showed that Virkon-S had a significant reduction on pathogenic load on shell ranged from 94 to 100%, albumen from 92.3 to 100% and yolk from 96.8 to 100%. However, Gasparini et al (1995) found that Virkon-S is effective but the prolonged use may leads to resistant pathogens. This finding coincides with those of Sidhu et al (2002;Moustafa Gehan et al, 2004;Ellen, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A rational choice of disinfectants for this purpose should be based on the data on their efficacy in vitro and in the field. Tests of the biocidal activity of peroxygen compounds under such conditions demonstrated their very good efficacy in killing bacteria, fungi, viruses and spores (Gasparini et al, 1995;Gutierrez et al, 1999;Hernandez et al, 2000;Amass et al, 2001). The present study demonstrated very good efficacy of two disinfectants with a mixture of peroxide salts (Virkon S) and potassium peroxomonosulphate (Chirox) as their active ingredients against both tested strains of B. hyodysenteriae.…”
Section: Discussionmentioning
confidence: 99%